Behind the Manufacturing of Industrial Clay Bricks: Drying Stage Predictions Using CFD. (1st March 2022) - Santos, R. S.; Delgado, J. M. P. Q.; Silva, F. A. N.; Azevedo, A. C.; Farias Neto, S. R.; Farias, F. P. M.; Barbosa de Lima, A. G.; Barbosa de Lima, W. M. P.; Lima, E. S.
Abstract : Drying of ceramic materials plays important role for industry, involving questions related to investments, energy consumption, product quality, and environmental pollution. In this sense, this work aims to predict heat and mass transfer during the drying process of an industrial clay brick in oven. Simulations were carried out by computational fluid dynamics (Ansys CFX software). Results of the drying and heating kinetics and the moisture content and temperature distributions of the product at different elapsed times are shown and analyzed. The results showed a good agreement between the experimental data, of the surface temperature and the average moisture content, and the numerical results. From the results, it was verified that the proposed mathematical modeling was adequate, providing predicted results in accordance with the experimental data used. Furthermore, numerical results showed that an increase in drying-air temperature and a decrease in relative humidity lead to an increase in heating and moisture removal rates. In the research, it was observed that mass diffusion coefficient increased with increasing drying-air temperature.